2007
DOI: 10.1126/science.1139438
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Competition and Selection During Memory Formation

Abstract: Competition between neurons is necessary for refining neural circuits during development and may be important for selecting the neurons that participate in encoding memories in the adult brain. To examine neuronal competition during memory formation, we conducted experiments with mice in which we manipulated the function of CREB (adenosine 3',5'-monophosphate response element-binding protein) in subsets of neurons. Changes in CREB function influenced the probability that individual lateral amygdala neurons wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

51
533
4
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 592 publications
(595 citation statements)
references
References 27 publications
51
533
4
7
Order By: Relevance
“…Neuronal allocation to an engram based on relative CREB function or excitability at the time of training was initially described in the LA for auditory fear memory (Han et al, 2007(Han et al, , 2009Zhou et al, 2009). Since that time, a similar allocation process was shown in several other brain regions supporting many types of memory, including in the LA for encoding of cocaine-conditioned place preference memories , in the LA for aversive memories (Zhou et al, 2009), in the insular cortex for encoding conditioned taste aversion (Sano et al, 2014), and in the piriform cortex during a shock avoidance paradigm (Choi et al, 2011).…”
Section: Neuronal Allocation To a Fear Memory Engram In The Dg Is Basmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuronal allocation to an engram based on relative CREB function or excitability at the time of training was initially described in the LA for auditory fear memory (Han et al, 2007(Han et al, , 2009Zhou et al, 2009). Since that time, a similar allocation process was shown in several other brain regions supporting many types of memory, including in the LA for encoding of cocaine-conditioned place preference memories , in the LA for aversive memories (Zhou et al, 2009), in the insular cortex for encoding conditioned taste aversion (Sano et al, 2014), and in the piriform cortex during a shock avoidance paradigm (Choi et al, 2011).…”
Section: Neuronal Allocation To a Fear Memory Engram In The Dg Is Basmentioning
confidence: 99%
“…We (Han et al, 2007(Han et al, , 2009Yiu et al, 2014) and others (Zhou et al, 2009;Gouty-Colomer et al, 2016), previously examined how neurons in the lateral nucleus of the amygdala (LA) are allocated to an engram supporting a discrete cue fear memory (in which an initially motivationally neutral auditory cue is paired with an aversive foot shock) (Davis, 1992;LeDoux, 2000;Maren, 2003). Increasing the function of the transcription factor CREB (Ca 2+ /cAMP response element-binding protein) in individual principal LA neurons increased the likelihood that a particular neuron would become part of a fear/threat memory engram (Han et al, 2007(Han et al, , 2009Zhou et al, 2009). Furthermore, genetic ablation or suppression of LA neurons overexpressing CREB (and not an equal number of random LA neurons) impaired memory expression (Han et al, 2009;Zhou et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that competition among neurons is important in memory formation, in which neurons are selected by their relative activities during the learning process. 6 This finding is related to Hebb's postulate, which suggests that the correlated activity among neurons performs synaptic modifications. 7 Such a postulate, called Hebbian learning, has been widely applied to artificial neural networks and machine learning.…”
Section: Introductionmentioning
confidence: 73%
“…The second study (Han et al 2009) is a follow-up to the first (Han et al 2007). In both experiments, the form of learning under study is an auditory fear-conditioning paradigm.…”
Section: A Minimal Versus a Substantivementioning
confidence: 99%
“…In the first study, they conducted a series of experiments in order to determine what role cyclic-AMP response element binding protein (CREB) plays in recruiting neurons in the LA into a "fear memory trace" (Han et al 2007). They had shown previously that cells in the mouse LA exhibit activated CREB after training in the learning paradigm, and they wanted to know whether CREB activation selectively determined in which population of cells a fear memory would be stored.…”
Section: A Minimal Versus a Substantivementioning
confidence: 99%